Transcriptomic Characterization of the Effects of Selenium on Maize Seedling Growth - Dou, Lingling; Tian, Zailong; Zhao, Qin; Xu, Mengting; Zhu, Yiran; Luo, Xiaoyue; Qiao, Xinxing; Ren, Rui; Zhang, Xianliang; Li, Huaizhu (Frontiers in Plant Science, 2021)
Selenium (Se) is a trace mineral element in soils that can be beneficial to plants in small amounts. Although maize is among the most economically important crops, there are few reports on the effects of Se on maize seedling growth at the molecular level. In this study, the growth of maize seedlings treated with different concentrations of Na2SeO3 was investigated, and the physiological characteristics were measured. Compared with the control, a low Se concentration promoted seedling growth, whereas a high Se concentration inhibited it. To illustrate the transcriptional effects of Se on maize seedling growth, samples from control plants and those treated with low or high concentrations of Se were subjected to RNA sequencing. The differentially expressed gene (DEG) analysis revealed that there were 239 upregulated and 106 downregulated genes in the low Se treatment groups, while there were 845 upregulated and 1,686 downregulated DEGs in the high Se treatment groups. Both the Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) annotation analyses showed a low concentration of the Se-stimulated expression of “DNA replication” and “glutathione (GSH) metabolism”-related genes. A high concentration of Se repressed the expression of auxin signal transduction and lignin biosynthesis-related genes. The real-time quantitative reverse transcription PCR (qRT-PCR) results showed that in the low Se treatment, “auxin signal transduction,” “DNA replication,” and lignin biosynthesis-related genes were upregulated 1.4- to 57.68-fold compared to the control, while, in the high Se concentration treatment, auxin signal transduction and lignin biosynthesis-related genes were downregulated 1.6- to 16.23-fold compared to the control. Based on these transcriptional differences and qRT-PCR validation, it was found that a low dosage of Se may promote maize seedling growth but becomes inhibitory to growth at higher concentrations. This study lays a foundation for the mechanisms underlying the effects of Se on maize seedling growth.